2022
DOI: 10.3390/molecules27051670
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Heparin Recovery from Porcine Intestinal Mucosa Using Zeolite Imidazolate Framework-8

Abstract: Heparin is one of the most valuable active pharmaceutical ingredients, and it is generally isolated from porcine intestinal mucosa. Traditionally, different types of commercial resins are employed as an adsorbent for heparin uptake; however, using new, less expensive adsorbents has attracted more interest in the past few years to enhance the heparin recovery. Zeolite imidazolate framework-8 (ZIF-8), as a metal–organic framework (MOF) with a high surface area, porosity, and good stability at high temperatures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The highest adsorption efficiency was achieved at the lowest concentration of ammonium chloride. This way, a higher yield of recovered heparin (86.17%) from porcine intestinal mucosa was achieved than in the process using zeolite imidazolate framework-8 (70%) as an adsorbent (Abdolmaleki et al, 2022).…”
Section: Heparin Isolationmentioning
confidence: 96%
See 2 more Smart Citations
“…The highest adsorption efficiency was achieved at the lowest concentration of ammonium chloride. This way, a higher yield of recovered heparin (86.17%) from porcine intestinal mucosa was achieved than in the process using zeolite imidazolate framework-8 (70%) as an adsorbent (Abdolmaleki et al, 2022).…”
Section: Heparin Isolationmentioning
confidence: 96%
“…In the case of adsorption kinetics of heparin onto the zeolite imidazolate framework-8 (Abdolmaleki et al, 2022) or ectoine onto the Dowex HCR-S (Wu et al, 2021), it was described by the pseudo-second-order model better than the pseudo-firstorder model.…”
Section: Kinetic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides heparin, this digestion mixture contains nucleic acids, proteins, and other biochemicals. The next step of the heparin extraction process involves several adsorption-desorption steps [7][8][9][10][11][12]. This complex and labor-intensive process makes the extraction unviable and only very low concentrations (0.01% w/w) of heparin are isolated from enzymatically digested natural tissue [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their advantages, low selectivity toward the recovery of HEP and costly manufacturing processes are the biggest challenges. Up to now, in our group, we have suggested and studied the application of several adsorbents such as ZIF-8, cross-linked spherical polycationic bead, and amine-functionalized carbon/titanium dioxide nanotube arrays on titanium foil for uptake of HEP [ 17 , 18 , 19 ]. These series of studies have demonstrated that having appropriate surface functionality is extremely helpful in increasing the adsorption efficiency of the sorbents.…”
Section: Introductionmentioning
confidence: 99%